Surface modification of bamboo fiber with dopamine associated by laccase for poly(3-hydroxylbutyrate) biocomposites. (20th February 2023) - Chen, Zhenghao; Du, Keke; Yin, Hongnian; Zhang, Dongyan; Gao, Jian; Song, Wei; Zhang, Shuangbao
Abstract: For the purposes of obtaining poly(3-hydroxylbutyrate) (PHB) matrix composites with high performance, a novel eco-friendly surface modification pathway for bamboo fiber (BF) was demonstrated. Dopamine was first polymerized to poly(dopamine) (PDA) by laccase and then was deposited on the surface of BFs, which would improve interfacial adhesion between PHB and BFs. The replacement of chemical reagents by laccase to catalyze polymerization of dopamine could avoid the environmental damage and the degradation of natural fiber structure under alkaline conditions. The results showed that, when using laccase, the PDA layer was successfully coated on the surface of BFs in an acidic environment without destroying the structure of BFs, while self-polymerization hardly happened in the presence of dopamine alone, according to the X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and X-ray diffraction. When the dosage of dopamine was 1.0 wt% of BFs (1-D-L), the PHB/1-D-L had a higher flexural strength 32.56 MPa and impact strength 16.46 J m −1, meanwhile, the composites had a lower crystallinity index ( Xc ) 17.08% when the dopamine was added 1.5 wt%. However, the mechanical properties and water resistance of PHB matrix composites could be decreased possibly due to steric hindrance when there was an excess of dopamine during surface modification. Graphical abstract: Image 1 Highlights: Dopamine polymerizes into poly(dopamine) by laccase in weak acid environments. The PDA can be grafted to cellulose because lignin is depolymerized by laccase. Mechanical performance and water resistance of PHB matrix composites increase. Interfacial adhesion is improved by modification with dopamine related to laccase. This surface modification strategy shows great potential in cleaner production.